Streamlined Approach for Infrapubic Placement of an Inflatable Penile Prosthesis. (28th May 2012) - Karpman, Edward
Abstract : The streamlined approach for infrapubic placement of an inflatable penile prosthesis is a variation of the traditional infrapubic approach. A better understanding of operative techniques and recent clinical outcome studies have led to an evolution of the original infrapubic approach. Small incisions and efficient operative maneuvers can shorten operative times and expedite postoperative recovery. Erratum to "Streamlined Approach for Infrapubic Placement of an Inflatable Penile Prosthesis" dx.doi.org/10.1155/2012/984809